History of origin and development of replacement of plants crop rotations is in world agriculture - Kovalenko, Natalia (Acta Agraria Debreceniensis, 2013)
In practice of world agriculture a long ago the known problem of decline of harvests of agricultural cultures at their permanent growing, scientific explanation of this phenomenon became possible only with appearance of natural sciences. At first the declines of harvests bound to the toxic action of root excretions cultures on her repeated sowing, with development of humus theory of feed of plants of diminishing of harvests at the permanent sowing began to explain impoverishment of soil on a humus. During a few centuries the known farmers development the looks in relation to forming of scientific bases of construction of replacement of plants crop rotations in the world systems of agriculture, set history of their development and improvement. The analysis of influence of possibility of optimal satiation of replacement of plants crop rotations is conducted by agricultural cultures on the level of fertility of soil, water and nourishing modes and their productivity. For the terms of the insufficient moistening a positive action is marked black pair on the improvement of the water mode of soil in crop rotations. In historiography the problem of introduction and mastering of replacement of plants crop rotations for the decision of scientific and practical tasks of agricultural production is represented in many-sided aspects, worked out and the recommended replacement of plants crop rotations that are base on zonal principle of development of world agriculture that passed the protracted term of test and counted on various specialization of economies. But for today development of scientific and technical progress requires intensification of agricultural production with the use of intensive crop rotations and growing of high-performance cultures. Hereupon there was a necessity of realization of analysis of the systems of historical value of scientifically-practical knowledge about development and improvement of replacement of plants crop rotations, as it gives an opportunity to work out to recommending a production with the use of the most effective elements of the past on modern agrarian business and allows to forecast them on the future.